The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/minf.201300082
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Similar Binding Sites to Detect Distant Polypharmacology

Abstract: The ability of small molecules to interact with multiple proteins is referred to as polypharmacology. This property is often linked to the therapeutic action of drugs but it is known also to be responsible for many of their side effects. Because of its importance, the development of computational methods that can predict drug polypharmacology has become an important line of research that led recently to the identification of many novel targets for known drugs. Nowadays, the majority of these methods are based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 177 publications
(201 reference statements)
1
47
0
Order By: Relevance
“…The similarities of other promiscuous ligands in Additional file 1: Table S2 also seem to be mainly hydrophobic and this is consistent with previous observations that promiscuity correlates with hydrophobicity [7, 45]. This correlation between promiscuity and hydrophobicity seems to hold for targets as well.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The similarities of other promiscuous ligands in Additional file 1: Table S2 also seem to be mainly hydrophobic and this is consistent with previous observations that promiscuity correlates with hydrophobicity [7, 45]. This correlation between promiscuity and hydrophobicity seems to hold for targets as well.…”
Section: Resultssupporting
confidence: 89%
“…The ability of a ligand to bind multiple targets likely depends on ligand-based and target-based properties, as both are inter-dependent. Ligand hydrophobicity is generally correlated with promiscuity [7]. Haupt et al also found a correlation between binding promiscuity and ligand flexibility [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study based on the similarity ensemble approach showed that similar ligands were able to bind proteins with distantly related sequences (Keiser et al, 2007). Overall, local binding site similarities can be more important than global similarities to determine polypharmacology and drug repurposing (Jalencas and Mestres, 2013b; Anighoro et al, 2015). …”
Section: Structure-based Approaches In Drug Repurposingmentioning
confidence: 99%
“…Chemoisosterism can be defined as the property of two protein environments to bind the same molecular fragment, and can shed light into the inherent cross-pharmacology between protein targets. The degree of chemoisosterism was found to be related to the polypharmacology of chemical fragments (Jalencas and Mestres, 2013b). This approach allows the creation of interaction networks connecting chemical fragments to chemoisosteric protein environments.…”
Section: Structure-based Approaches In Drug Repurposingmentioning
confidence: 99%
“…In the light of systems biology, it seems reasonable to first select a combination of receptors that will modify the biological network as desired, and then design a ligand that it is able to simultaneously bind them [3]. Unfortunately, in practice, most target combinations that are identified in the network analysis step will not show cross-pharmacology, since the discovery of intended promiscuous drugs is still restricted to members of the same protein family [4]. Besides few remarkable exceptions [59], the rational molecular design of ligands that intentionally bind several unrelated proteins is far too complicated, yielding ambivalent, non-drug like molecules.…”
Section: Introductionmentioning
confidence: 99%